The bitter principles of Tinospora rumphii Boerl. - De Guzman, Anita D.
Extraction of the Makabuhay plant with various solvent systems was tried. A crude extract was obtained with ethanol as solvent. Although the presence of glycosides is indicated, work up on the crude extract failed to yield enough crystals for further study.